Problematic Pornography Use, Psychopathology, and Body Connection: Associations and Sex Differences - Engelhardt, Robin; Maes, Jürgen; Borgogna, Nicholas C.; von Oertzen, Timo; Potenza, Marc N.; Kraus, Shane W. (Addicta: The Turkish Journal on Addictions, 2025)
Problematic pornography use is an increasingly relevant phenomenon in the United States. Especially young and male individuals seem to be vulnerable to experiencing problems with their pornography use. Previous research suggests that additional psychological symptoms may relate to problematic pornography use in some populations, and little is known about associations with body connection. Therefore, the current study examined associations between problematic pornography use and symptoms of psychological distress, impulsivity, and body connection in a large sample of male and female US university students (n =1525). Results indicated positive associations between problematic pornography use on the one hand and psychological symptoms and body dissociation on the other hand. However, when predicting problematic pornography use by all variables in a regression model, the association with body dissociation became negative in male and unrelated in female students while associations with body awareness became statistically significant and positive in both groups. In addition, a sex difference for the association with psychological distress was found. Further work is needed to examine the association between problematic pornography use and body connection, as well as the potential sex effect found in relation to psychological distress. Therefore, we recommend further sex-informed and longitudinal analyses investigating problematic pornography use.
Keywords: Addictive behavior; body connection; compulsive sexual behavior; pornography; psychological distress; psychopathology